PENGARUH INTENSITAS KEBISINGAN TERHADAP TEKANAN DARAH SEBELUM DAN SETELAH BEKERJA DI PERCETAKAN CV. RINJANI PERKASA - Citra Wardani; Sri Zelviani; Nurul Fuadi (Universitas Islam Negeri Alauddin Makassar, 2021)
This research was attempted to identify the effect of the seriousness of noise on CV Rinjani Perkasa's blood pressure. This study used a procedure to compare blood pressure before and after exposure to sound sources from the press. Fifteen respondents measured blood pressure between the ages of 20-40 years during working hours using a digital blood monitor. The average measured sound seriousness is 107.8 dB in the room where the sound source is made and 99.1 dB in the room directly adjacent to the sound source. Blood pressure measurements showed that blood pressure increased more in 15 respondents. For example, Respondent 4 who is located next to the noise source has a systolic blood pressure of 20.62% and a diastolic blood pressure of 15.96%, whereas Respondent 1 is located next to the noise source. There is a problem, the percentage increase. With blood pressure. Low blood pressure Systolic blood pressure of 7.48% and diastolic blood pressure of 6.08%.